A system for simultaneously measuring contact force, ultrasound, and position information for use in force-based correction of freehand scanning. - Burcher, MR; Noble, J; Han, L; Gooding, M (2005)
During freehand ultrasound imaging, the sonographer places the ultrasound probe on the patient's skin. This paper describes a system that simultaneously records the position of the probe, the contact force between the probe and skin, and the ultrasound image. The system consists of an ultrasound machine, a probe, a force sensor, an optical localizer, and a host computer. Two new calibration methods are demonstrated: a temporal calibration to determine the time delay between force and position measurements, and a gravitational calibration to remove the effect of gravity on the recorded force. Measurements made with the system showed good agreement with those obtained from a standard materials testing machine. The system's uses include three-dimensional (3-D) ultrasound imaging, force-based deformation correction of ultrasound images, and indentation testing.